Ukhuwah Islamiyah - Nurfadhilah Paisal; Yuyun Andira Sasminto; Ansar; Asbar Sakti; M. Amin (STKIP Subang, 2025)
Ukhuwah Islamiyah is a concept of brotherhood taught in Islam as a fundamental foundation for building a harmonious, peaceful, and just social life. This concept not only encompasses brotherhood among Muslims but also emphasizes Islamic values in broader human relations. This article aims to examine the concept of Ukhuwah Islamiyah from the perspectives of the Qur’an and Hadith, as well as to describe its forms and efforts to strengthen it in social life. The research method used is library research by reviewing various relevant literature, scientific journals, Qur’anic exegesis, and Hadith. The results of the study indicate that Ukhuwah Islamiyah is a form of brotherhood based on faith, compassion, tolerance, justice, and mutual respect. Strengthening ukhuwah can be achieved through forgiveness, protecting the dignity of others, strengthening social bonds, maintaining polite communication, and instilling Islamic values through education. By consistently practicing Ukhuwah Islamiyah, Muslims can foster unity and social harmony amid diversity and contemporary challenges.